The Entamoeba histolytica TBP and TRF1 transcription factors are GAAC-box binding proteins, which display differential gene expression under different stress stimuli and during the interaction with mammalian cells - Ravi Kumar Narayanasamy; Carlos Alberto Castañón-Sanchez; Juan Pedro Luna-Arias; Guillermina García-Rivera; Bartolo Avendaño-Borromeo; María Luisa Labra-Barrios; Jesús Valdés; María Esther Herrera-Aguirre; Esther Orozco (Parasites & Vectors, 2018)
Abstract Background Entamoeba histolytica is the protozoan parasite responsible for human amebiasis. It causes up to 100,000 deaths worldwide each year. This parasite has two closely related basal transcription factors, the TATA-box binding protein (EhTBP) and the TBP-related factor 1 (EhTRF1). TBP binds to the canonical TATTTAAA-box, as well as to different TATA variants. TRF1 also binds to the TATTTAAA-box. However, their binding capacity to diverse core promoter elements, including the GAAC-element, and their role in gene regulation in this parasite remains unknown. Methods EMSA experiments were performed to determine the binding capacity of recombinant TBP and TRF1 to TATA variants, GAAC and GAAC-like boxes. For the functional analysis under different stress stimuli (e.g. growth curve, serum depletion, heat-shock, and UV-irradiation) and during the interaction with mammalian cells (erythrocytes, MDCK cell monolayers, and hepatocytes of hamsters), RT-qPCR, and gene knockdown were performed. Results Both transcription factors bound to the different TATA variants tested, as well as to the GAAC-boxes, suggesting that they are GAAC-box-binding proteins. The K D values determined for TBP and TRF1 for the different TATA variants and GAAC-box were in the range of 10-12 M to 10-11 M. During the death phase of growth or in serum depletion, Ehtbp mRNA levels significantly increased, whereas the mRNA level of Ehtrf1 did not change under these conditions. Ehtrf1 gene expression was negatively regulated by UV-irradiation and heat-shock stress, with no changes in Ehtbp gene expression. Moreover, Ehtrf1 gene also showed a negative regulation during erythrophagocytosis, liver abscess formation, and a transient expression level increase at the initial phase of MDCK cell destruction. Finally, the Ehtbp gene knockdown displayed a drastic decrease in the efficiency of erythrophagocytosis in G3 trophozoites. Conclusions To our knowledge, this study reveals that these basal transcription factors are able to bind multiple core promoter elements. However, their immediate change in gene expression level in response to different stimuli, as well as during the interaction with mammalian cells, and the diminishing of erythrophagocytosis by silencing the Ehtbp gene indicate the different physiological roles of these transcription factors in E. histolytica.